1993
DOI: 10.1128/iai.61.7.3038-3046.1993
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial proteins of murine macrophages

Abstract: Three murine microbicidal proteins (MUMPs) were purified from cells of the murine macrophage cell line RAW264.7 that had been activated by gamma interferon. Similar proteins were also present in nonactivated RAW264.7 cells, in cells of the murine macrophage cell line J774A.1, and in resident and activated murine peritoneal macrophages. MUMP-1, MUMP-2, and MUMP-3 killed SalmoneUla typhimurium, Escherichia coli, Staphylococcus aureus, Listeria monocytogenes, Mycobacterium fortuitum, and Cryptococcus neofornans i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(61 citation statements)
references
References 53 publications
1
60
0
Order By: Relevance
“…In the conditions we tested, 100-fold higher concentrations did not affect either form of C. albicans. Hiemstra et al (1993) showed that histone-like peptides from murine macrophages kill the yeast Cryptococcus neoformans. These antimicrobial peptides are homologous but are not identical to histones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the conditions we tested, 100-fold higher concentrations did not affect either form of C. albicans. Hiemstra et al (1993) showed that histone-like peptides from murine macrophages kill the yeast Cryptococcus neoformans. These antimicrobial peptides are homologous but are not identical to histones.…”
Section: Discussionmentioning
confidence: 99%
“…Together NET-associated antibacterial granule proteins and the histones degrade virulence factors and kill bacteria. Indeed, the bactericidal properties of histones have been recognized for decades (Hirsch, 1958;Hiemstra et al ., 1993;Kim et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Four histones, H2A, H2B, H3 and H4 are important for chromosome organization in the nucleosome. Previous studies have suggested that histones have additional functions, including hormone activity [25], activation of leucocytes in salmon [26] and as part of the antimicrobial defence in mammals [27][28][29]. Even if the antimicrobial effect of histones has been known for decades [30], they were just recently linked to the innate immune system of frog [31], fish [2,3,15,16,[32][33][34][35][36] and mammals [29,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Beckerman and coworkers [3] noted that a nitric oxide synthase inhibitor only partially blocks the IFN-7-induced enhancement of the Listericidal activity of macrophages in vitro. These investigators interpreted this as an indication of a Listericidal mechanism in addition to RNI [3], Also, it is conceivable that nitric oxide synthase inhibitors, most of which are positively charged arginine derivatives, could affect other anti-microbial mechanisms in addition to RNI, For example, these molecules might bind to the same bacterial target site(s) as positively charged anti-bacterial peptides [13] or proteins [14], thereby decreasing the effectiveness of these important anti-microbial mechanisms. It seems likely that future studies to reconcile the apparent contradictions in this area of research will reveal multiple mechanisms of Listericidal activity that may be interdependent, and could be influenced significantly by experimental factors such as mouse strain and macrophage activation protocol.…”
Section: Discussionmentioning
confidence: 99%